A decision support system for construction contractor pre-qualification - Weng, Shih-chuan; Ogunlana, Stephen O.; Nagarur, Nagendra N.; Soegaard, Ragnar; The Ministry of Communications, R.O.C. (Bangkok : Asian Institute of Technology, 1992)
Tharavijitkul made a feasibility study on DSS for bid selection in 1991. She had revealed the contractor or bidder pre-qualification and/or classification procedures and together with the accompanied criteria used during pre-qualification. Her study concen trated on the pre-qualification procedures used in two government offices: the EGAT and the RIDT. This DSSpre-qualifier is produced in line with her recommendation. The DSSpre-qualifler employs dBASE III Plus business package and the DSS sys tem. It uses the "Black Box" criteria and scoring system to evaluate each clue on each information item submitted by the contractor or bidder. It also supplies "Open Box" to compare some qualitative information which are offered by the author and more over, the input/output mechanism·were designed to make those criteria modifiable by the user or manager in order to support his or her decision making. DSSpre-qualifier also provides an on-line query system which combines the built-in Assistant menu program to offer the user or manager to make any requests in the fulfillment of his or her needs.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Civil Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1992
Keywords: Engineering -- Contracts and specifications; Decision support systems